Focus on Form and Focus on Forms in Implicit Grammar Teaching Strategy - Rizki Indra Guci; Dewi Rochsantiningsih; Sumardi Sumardi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Grammar instruction in foreign language teaching has been identified by most studies as one aspect that plays an important role in promoting the learning process of reading, writing, speaking and understanding a foreign language. Consequently, secondary and foreign language teaching of grammar is seen as a topic of debate. So academics and teachers seem to have been willing to work out the proper way of teaching grammar. This condition contributes to a likely cause of uncertainty for teachers and students, and then brings researchers to a rigorous theoretical discussion on the question of how grammar should be presented: explicitly or implicitly. The purpose of the present case study was to gather information into the implementation of the implicit grammar teaching strategy enrolled in senior high school. To this extent, interview sessions and observation were used to obtain all the data required for the study. The results, in a broad sense, confirmed that the teacher showed positive views on the implementation of the implicit grammar teaching strategy. However, classroom practices were quite different from the findings of previous related research consistent with the supremacy of either Focus on Form or Focus on Forms in the delivery of lesson materials. As an implication, this study encouraged Indonesian English teachers to start considering the implementation of implicit grammar teaching strategy so that students could be directed to the language acquisition cycle instead of the language learning.